2013
DOI: 10.1071/he13054
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels during pregnancy and gestational weight gain among women who are overweight or obese

Abstract: Issue addressed: There is contradictory research assessing physical activity patterns during pregnancy and postpartum among women who are overweight or obese. The aim of this study was to evaluate physical activity among overweight and obese women over the course of pregnancy and the initial postpartum period. Methods: Three hundred and five overweight or obese pregnant women completed physical-activity questionnaires at three time points during pregnancy and at 4-months postpartum. Results: Physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…Similarly, a small study, carried out using both a questionnaire and heart rate monitoring in 23 Swedish normal-weight women, reported a small PA decline between 14 and 32 weeks of gestation [21]. Similar findings were also reported in a study carried out in 305 overweight or obese women who filled in a questionnaire at different time points during pregnancy, and reported a decline in PA between early and middle-late pregnancy [13]. Finally, a small prospective study, aimed at comparing accelerometers and self-reported PA measures and carried out at different time points during pregnancy in a sample of 57 women from the UK, reported a significant decline in PA volume from 12–16 to 34–38 week of gestation [11].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similarly, a small study, carried out using both a questionnaire and heart rate monitoring in 23 Swedish normal-weight women, reported a small PA decline between 14 and 32 weeks of gestation [21]. Similar findings were also reported in a study carried out in 305 overweight or obese women who filled in a questionnaire at different time points during pregnancy, and reported a decline in PA between early and middle-late pregnancy [13]. Finally, a small prospective study, aimed at comparing accelerometers and self-reported PA measures and carried out at different time points during pregnancy in a sample of 57 women from the UK, reported a significant decline in PA volume from 12–16 to 34–38 week of gestation [11].…”
Section: Discussionsupporting
confidence: 63%
“…Only a few previous studies have assessed PA patterns throughout gestation, with inconsistent findings [8,10,11,12,13,14,21]. These studies have reported either a progressive decrease in PA during pregnancy [8,11], or no change [10], or higher PA levels in the second than in the first or the third trimester of gestation [12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior meta-analyses have indicated the importance of physical activity in pregnancy in optimising gestational weight gain and improving birth outcomes [17]. While often considered in the whole context of lifestyle, additional research should focus specifically on physical activity in pregnancy, given the decline that commonly occurs in women during this life phase [34][35][36]. Recent research suggests that declining activity in pregnancy now negates any need to increase energy intake, particularly in the first trimester [37].…”
Section: Discussionmentioning
confidence: 99%
“…There are many risk factors for preeclampsia indicating heterogeneity of this disease with obesity being one of them (Jeyabalan, 2013). In respect to other risk factors like pregnancy specific issues (previous number of pregnancies, number of fetuses, specific genetic disorders), maternal preexisting conditions (age, race, BMI, pregestational diabetes, hypertension, renal disease, antiphospholipid syndrome, some autoimmune diseases) family history of preeclampsia and smoking, obesity is modifiable and the only risk factor that can be positively affected by physical activity (Sui, Moran, & Dodd, 2013). As expected, together with obesity, excessive gestational weight gain results from decreased physical activity during pregnancy which additionally highlights the importance of adapted and controlled physical activity during pregnancy.…”
Section: Type:  Aerobicmentioning
confidence: 99%